French maritime pine bark extract (pycnogenol) in association with triple combination cream for the treatment of facial melasma in women: a double-blind, randomized, placebo-controlled trial - Lima, P. B. [UNESP]; Dias, J. A.F. [UNESP]; Esposito, A. C.C. [UNESP]; Miot, L. D.B. [UNESP]; Miot, H. A. [UNESP] (Wiley, 2021)
Background: Melasma can be recalcitrant to treatment, and relapses are common. Pycnogenol has been reported to be effective in treating melasma. Objective: To compare the efficacy, safety and tolerability of 75 mg pycnogenol taken orally twice a day vs. a placebo, in association with the triple combination and broad-spectrum sunscreen for the treatment of facial melasma. Methods: A randomized, double-blind, parallel, placebo-controlled study was conducted on 44 women with facial melasma in a single centre from May 2019 through November 2019. Patients with melasma were randomly assigned to orally take 75 mg pycnogenol (PYC) or a placebo (PLAC) twice a day for 60 days. Both groups also received tinted sunscreen [Sun Protection Factor (SPF) 50; Persistent Pigment Darkening (PPD) 17] for daytime use and a topical triple combination at bedtime. The primary outcome was a change from the baseline Modified Melasma Area Severity Index (mMASI) score. Secondary outcomes were improvements in the patients' quality of life (MELASQoL), colorimetric indices and Global Aesthetic Improvement Scale (GAIS). Results: All participants completed the trial. The mean (SD) age of the participants was 39 (7) years, and 91% were phototypes III–IV. Both groups exhibited a reduction in mMASI scores, MELASQoL scores and colour contrast (P < 0.01). The mean (CI 95%) reductions of the mMASI scores were 49% (36–61%) for PYC and 34% (16–47%) for PLAC. The reductions in mMASI scores and colorimetric contrast were superior for the PYC group (P < 0.05). The analysis of GAIS resulted in an improvement of 86% (CI 95%: 68–96%) for the participants in the PYC group and 55% (CI 95%: 32–73%) for those in the PLAC group. There were no adverse effects related to oral treatment. Conclusion: Pycnogenol is well-tolerated and increases the effectiveness of broad-spectrum sunscreen and the triple combination in the treatment of facial melasma in women.